Features of histologiacal morfology of components of the coronary arterial wall in experimental atherosclerosis. - Tryasak, N. S.; Silkina, Yu. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Atherosclerosis is a multifactorial chronic disease, which is associated with immune inflammation of the arteries. The main role in the development of atherosclerotic lesions belongs to the dendritic cells. Objective. To investigate the components of coronary arteries wall and their interrelationships in the experimental atherosclerosis. Methods. Animals received human native low density lipoproteins. Standard histological and immunehistochemical methods were used to detect dendritic cells and other components into coronary arteries wall. Results. On the 4-6th weeks of the experiment it was observed that dendritic cells form contacts with isolated lymphocytes and macrophages, and they were located mainly in the subendothelial layer. On the 12th week the artery wall has changed its structure and the composition of the cellular elements. After 16th week, dendritic cells were found in all layers of the coronary arteries and foam cells were revealed at this period. 18-20th weeks of the experiment were characterized by the phenomena of liposclerosis. Conclusion. It was established that under the normal condition the intima of coronary arteries in rats contains dendritic cells. There is a complex relationships between dendritic cells with other cells. The number of dendritic cells increases with the progression of atherosclerotic lesions. It was observed the redistribution of cells in the intima depends on the stage of atherosclerosis.